2014
DOI: 10.1002/bies.201400028
|View full text |Cite
|
Sign up to set email alerts
|

Spoken language achieves robustness and evolvability by exploiting degeneracy and neutrality

Abstract: As with biological systems, spoken languages are strikingly robust against perturbations. This paper shows that languages achieve robustness in a way that is highly similar to many biological systems. For example, speech sounds are encoded via multiple acoustically diverse, temporally distributed and functionally redundant cues, characteristics that bear similarities to what biologists call "degeneracy". Speech is furthermore adequately characterized by neutrality, with many different tongue configurations lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 82 publications
2
43
0
Order By: Relevance
“…a given speech category is often conveyed by multiple acoustic cues simultaneously. This property may make speech robust to both external background noise (Winter, 2014) and internal "noise" related to imprecise representation of auditory information (Patel, 2014). In support of this idea, we found that performance on the both cues condition surpassed that of either single-cue condition for phase perception, in alignment with previous findings that rising pitch and increased duration are more effective cues to phrase boundaries when presented simultaneously .…”
Section: The Role Of Pitch and Durational Cues In Focus And Phrase Pesupporting
confidence: 90%
“…a given speech category is often conveyed by multiple acoustic cues simultaneously. This property may make speech robust to both external background noise (Winter, 2014) and internal "noise" related to imprecise representation of auditory information (Patel, 2014). In support of this idea, we found that performance on the both cues condition surpassed that of either single-cue condition for phase perception, in alignment with previous findings that rising pitch and increased duration are more effective cues to phrase boundaries when presented simultaneously .…”
Section: The Role Of Pitch and Durational Cues In Focus And Phrase Pesupporting
confidence: 90%
“…An alternate explanation is that speech is robust to individual differences in auditory perception because it is structurally redundant: multiple acoustic dimensions convey information about a given category. This property may make speech robust not only to external background noise (Winter, 2014) but also to internal "noise" that is thought to relate to imprecise representation of an auditory dimension (Patel, 2014). This raises the possibility that listeners may be able to compensate for impairments along a single auditory dimension by assigning greater perceptual weight to auditory dimensions that they are better able to process.…”
Section: Speech Perception As Categorizationmentioning
confidence: 99%
“…As mentioned, the acoustic speech signal carries multiple co-occurring acoustic dimensions (e.g. roughly described as pitch, duration, and amplitude), which often provide redundant cues to disambiguate a linguistic category (Patel, 2014;Winter, 2014;Jasmin et al, 2019a). Individuals with typical pitch perception have learned through a lifetime of experience with speech acoustics that vocal pitch is a useful and reliable cue.…”
Section: [H1] Introductionmentioning
confidence: 99%